Abcb1a but not Abcg2 played a predominant role in limiting the brain distribution of Huperzine A in mice. (September 2017) - Li, Jiajun; Yue, Mei; Zhou, Dandan; Wang, Meiyu; Zhang, Hongjian
Abstract: Huperzine A has been used for improving symptoms of Alzheimer's disease. Its cholinergic side effect is thought to be an exaggerated pharmacological outcome linked to its high brain or CNS concentrations. Although Huperzine A is brain penetrable, its interaction with efflux transporters (ABCB1 and ABCG2) has not been fully investigated. The aim of the present study was to characterize roles of ABCB1 and ABCG2 in the transmembrane transport of Huperzine A and identify a rate limiting step in its brain distribution. Data obtained from stably transfected MDCK II cells showed that Huperzine A is a substrate of ABCB1 but not ABCG2. ABCB1 inhibitors significantly inhibited ABCB1 mediated efflux of Huperzine A. In Abcb1a −/− mice, the brain to plasma concentration ratio of Huperzine A was significantly increased as compared to the wild type mice, while there were no obvious differences between the wild type and Abcg2 −/− mice. Taken together, the present study demonstrated that ABCB1 but not ABCG2 played a predominant role in the efflux of Huperzine A across BBB. The current finding is clinically relevant as changes in ABCB1 activity in the presence of ABCB1 inhibitors or genetic polymorphism may affect efficacy and safety of Huperzine A. Graphical abstract: Highlights: ABCB1 (P-gp) played a major role in the efflux transport of Huperzine A in Caco-2 and transfected MDCKII cell lines. Abcb1a was a limiting factor for Huperzine A's brain distribution in Abcb1a −/−, Abcg2 −/−, and Abcb1a −/− / Abcg2 −/− mice. Modulation of ABCB1 activity may lead to changes in brain concentrations of Huperzine A, thus altering its safety profiles.